Immune Response of Broiler Chicks to DL-Methionine Supplementation at Different Ages - Al-Mayah, Ali A.S. (International Journal of Poultry Science, 2006)
The study was conducted to evaluate the effect of methionine (ME) supplementation on immune response of broiler chicks during the period of 1st -7th and 29th - 36th day of age. The amino acid powder was supplemented as 1gm/L of drinking water or as 1gm/kg of feed during these early and late period of supplementation. The mean value of bursa of Fabricius, spleen and thymus weights of chicks supplemented DL-ME during the early period of age showed significant increment (P< 0.05). Whereas chicks which were supplemented during the late period of the maturation of the immune system did not show significant increasing in lymphoid organ weights. Of all the blood parameters examined, the red blood cell counts and mean cell volume showed significant increment (P< 0.05) from the control. Other haematological values were more than that of the normal values. The values of serum and liver total protein, albumin and globulin were highest but did not vary significantly from one another and from the control. We concluded that better immune response could be obtained with adequate supplementation of ME which have been identified to be in marginal quantities in poultry feed.